The relationship of the kicking action in soccer and anterior ankle impingement syndrome: a biomechanical analysis - Tol, J. L.; Slim, E.; van Soest, A. J.; van Dijk, C. N. (2002)
Two different hypotheses have been advanced to explain the formation of talotibial osteophytes in the anterior ankle impingement syndrome. We investigated how frequently hyperplantar flexion occurs during kicking and whether the site of impact of the ball coincides with the reported location of the osteophytes. We also measured the magnitude of the impact force. We studied 150 kicking actions performed by 15 elite soccer players by using mobile sensors and high-speed video. In 39% of the kicking actions, the plantar flexion angle exceeded the maximum static plantar flexion angle. Ball impact was predominantly made with the anteromedial aspect of the foot and ankle, with impact between the ball and the base of the first metatarsal bone in 89% of the kicking actions and between the ball and the anterior part of the medial malleolus in 76%. Postimpact ball velocity averaged 24.6 m/s, with a corresponding average contact force of 1025 N. Hyperplantar flexion was reached in only the minority of the kicking actions. The data on impact location and impact force support the hypothesis that spur formation in anterior ankle impingement syndrome is related to recurrent ball impact, which can be regarded as repetitive microtrauma to the anteromedial aspect of the ankle. Am J Sports Med 2002 Jan-Feb;30(1):45-50